Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan Pada Bank Mayapada Salemba Jakarta - Falah, Muhamad Sidiq Dinur; Damayanti, Wiwit; Koto³, Deni Indra Purnama (Journal MISSY (Management and Business Strategy), 2025)
This study aims to analyze the effect of work environment on employee performance at Bank Mayapada Salemba Jakarta. A quantitative approach with a saturated sampling technique was used, involving 78 employees. Data analysis employed simple linear regression. The results show that the work environment has a positive and significant effect on employee performance, indicated by a regression equation of Y = 4.531 + 0.896X. The t-count value of 18.438 > t-table 1.665 with a significance level of <0.05 proves that the work environment significantly affects employee performance. Furthermore, the coefficient of determination (R²) is 0.817, meaning that 81.7% of employee performance variation can be explained by the work environment, while the remaining 18.3% is influenced by other factors not examined in this study. Keywords: Work Environment, Employee Performance, Regression Analysis